A two-component system MechNtrB/MechNtrC related to nitrogen metabolism regulation in Micromonospora echinospora DSM43816 - Long, Yuxin; Lu, Jiayi; Leng, Siyi; Li, Congsi; Ni, Haiyan; Zou, Long; Wu, Zhiming; Long, Zhong-er (Frontiers in Microbiology, 2025)
The NtrB/NtrC two-component signal transduction system (TCS), predominantly found in Gram-negative bacteria, plays a crucial role in nitrogen metabolism regulation. Through BLASTP analysis of the complete proteome of Micromonospora echinospora DSM 43816 against the NtrB/NtrC database, homologous proteins were identified and designated as MechNtrB and MechNtrC. Subsequent in vitro expression and phosphorylation assays demonstrated that both proteins undergo phosphorylation, indicating a phosphoryl transfer mechanism for signal transduction between them. Yeast two-hybrid (Y2H) screening using selective media further verified specific in vivo protein–protein interactions between MechNtrB and MechNtrC. Quantitative real-time PCR (RT-qPCR) analyses revealed that overexpression of MechNtrB or MechNtrC gene significantly modulated the expression levels of key nitrogen metabolism genes, including those encoding glutamine synthetase (GS), glutamate synthase (GOGAT), and glutamate dehydrogenase (GDH). These collective findings establish that MechNtrB/MechNtrC constitutes a functional TCS in M. echinospora that directly regulates bacterial nitrogen metabolism.